Determinan Adopsi Green Banking Nasabah Bank Syariah Indonesia di Semarang: Peran Persepsi Sebagai Mediasi - Damayanti, Afina; Furqon, Ahmad; Mardhiyaturrositaningsih, Mardhiyaturrositaningsih (Akuntansi & Ekonomika, 2026)
The implementation of green banking is essential for Islamic banking in supporting sustainability. This study is based on an environmental survey showing that air quality in Semarang is categorized as moderate and may negatively affect public health. The study aims to analyze the influence of awareness, social influence, and environmental factors on the adoption of green banking among BSI customers in Semarang. A quantitative approach using SEM-PLS was applied to 130 respondents. The findings indicate that awareness, social influence, and environmental factors do not significantly affect green banking adoption directly. However, perception significantly moderates the relationship between awareness and adoption decisions. These results highlight the importance of positive customer perceptions of green banking benefits as a strategic reference for banks in improving education and developing sustainable green banking services in the future.